(untitled) (Research, Society and Development, 2022)
From the 1970s onwards, agribusiness in Brazil expanded, giving rise to the growth of agricultural production. The state of Piauí, in this context, began its process of agricultural modernization with the expansion of grains cultivation- mainly soybeans - in areas of the cerrado, a practice that was consolidated in the 1990s. One of the prominent municipalities in the state’s soybean production is Uruçuí, and in view of the importance of agribusiness in the Gross Domestic Product (GDP), this research was developed with the objective of analyzing and highlighting the evolution of soybean cultivation in Uruçuí, using technologies such as geographic information systems and the digital processing of remote sensing images, between 1985 and 2020. For that, it started with a bibliographic and cartographic investigation. A survey of production data was conducted on the website of the Brazilian Institute of Geography and Statistics (IBGE), using maps of land cover and use, statistical data and mosaics from collection 6 of the MapBiomas system, relating to the period. The consolidation of land productive modernization and the changes in the landscapes derived from agriculture in Uruçuí in the last 20 years have been confirmed, with emphasis on the production of soy. Furthermore, it was verified the geotechnologies agility and precision in the automatic capture of data related to the terrestrial surface for the management, analysis, and presentation of the generated information, which can be of great benefit to rural development policies and to the growth of the agribusiness in a sustainable way.